Effectiveness Of Rural Healthcare Centres: An Empirical Study In Sonitpur District Of Assam, India. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
It is essential for a nation to have provision for proper healthcare facility in urban as well as in rural areas of the country as health and socio-economic development work simultaneously. With the distressing effect of COVID-19, it becomes more important to understand how our health care system works and what it has more to provide. India is heavily covered with more rural populations than urban where Community Healthcare Centres (CHCs) being the uppermost tier of rural public health infrastructure in India is formed to provide proper healthcare service to its community. In the present study, an attempt has been made to understand the effectiveness of the health centers in the studied area so as to find out the areas which requires more attention and efforts can be put on those areas so as to improve the quality of service and provide proper healthcare facilities to the community. The result showed distressing figure and despite the well-structured healthcare system in the country, the health care infrastructure and the basic health care facilities even in the CHCs and Model hospital lagged far behind and required proper attention towards it.